The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/bog-2013-0017
|View full text |Cite
|
Sign up to set email alerts
|

The scale and the dynamics of permanent migration in rural and peri-urban areas in Poland – some problems

Abstract: Biegańska, J., and Szymańska, D. 2013: The scale and the dynamics of permanent migration in rural and peri-urban areas in Poland -some problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…This means that it is much easier to install such systems in new buildings, for instance in single-family houses. A pattern can be observed that in places where the number of new residential buildings is systematically growing (mainly in the suburban areas of large cities (Biegańska, Szymańska, 2013), the number of investments in solar technology projects, mainly solar collectors but increasingly often also photovoltaic systems, is rising too.…”
Section: Solar Technologies and The Development Of Distributed Generamentioning
confidence: 99%
“…This means that it is much easier to install such systems in new buildings, for instance in single-family houses. A pattern can be observed that in places where the number of new residential buildings is systematically growing (mainly in the suburban areas of large cities (Biegańska, Szymańska, 2013), the number of investments in solar technology projects, mainly solar collectors but increasingly often also photovoltaic systems, is rising too.…”
Section: Solar Technologies and The Development Of Distributed Generamentioning
confidence: 99%
“…The second factor was the systematic increase in rural populations. This was partly due to natural growth but also to increased migration from urban to rural areas [21]. As a result, the share of rural population in the total population of Poland increased from around 38% in 1989 to 39.9% (15.3 million people) in 2017.…”
Section: Resultsmentioning
confidence: 99%
“…In the years preceding 2015 election, in the majority of Polish cities with populations above 100,000, one could observe a population decline, mainly driven by great number of city dwellers moving to the neighboring small towns and rural areas (Biegańska and Szymańska, 2013), which possibly implied some spatial autoregression pattern driven by an increasing population of commuters.…”
Section: Electoral Geography In Poland: Background Information and LImentioning
confidence: 99%